HUBUNGAN PENGETAHUAN DENGAN PELAKSANAAN PERSETUJUAN SETELAH PENJELASAN (INFORMED CONSENT) PADA PASIEN DI IRDB BLU RSUP PROF DR R.D KANDOU - Herman Warouw (POLTEKKES KEMENKES MANADO, 2013)
Informed consent is a term which pointed on process of deciding action by patient after receives complete information about medical action given by doctor. This research aimed to acknowledge any correlation of knowledge with agreement implementation after explanation or informed consent (IC) on patients in IRDB BLU of Prof. Dr. R. D Kandou Hospital. Research method which being used is quantitative analytic with cross sectional approach by using 70 respondent in IRDB BLU of Prof. Dr. R. D Kandou Hospital as research respondent. Data gathering been conduct by respondent, in form of filling out prepared questioner and chi square test with mean level (p) 0, 05. Research result shows that from 70 respondents that being examined, as many as 61 respondent or 87, 1% with fine knowledge and 64 respondent or 91, 428% agreed and signed agreement after explanation. Conclusion of the research shows that knowledge of someone very affecting him on making decision. It is being advised for this research to evaluation of agreement implementation after this explanation and can explain content of agreement after this explanation with understandable language by patient and family so they can take decision according to acquired information